Predicting Customers Recommendation from Co-creation of Value, Customization and Relational Value. (March 2017) - Kaur Sahi, Gurjeet; Sehgal, Sanjeewani; Sharma, Rita
Executive Summary: There are countless illustrations where companies are involving their customers in the creation of products and delivery of services, commonly viewed as co-creation of value (CCV). The present work explores the value co-creation concept in the house construction business that requires maximum customer engagement with the service provider as compared to other subsectors in the real estate. With this background, the present study examined the comprehensive framework of antecedents and consequences of CCV leading to customers' recommendation in the housing sector. Moreover, the effect of CCV on customers' recommendation of a service provider is also studied by analyzing the role played by relational value and customized offerings. One of the main findings of the study is that the three pre-conditions, namely customer participation, customer expertise, and resource integration, significantly affect CCV. It was also found that when customers are allowed to participate and are provided with more choices, it leads to a higher level of trust. Thus, CCV has a significant impact on trust. Customers usually promote a service provider through positive word-of-mouth and make actual recommendations to others when he is able to ensure satisfactory services. Hence, the direct relationship of customer satisfaction with recommendation turns out to be significant. Another highlight of the study is that value co-creation is a platform where customers should proactively participate and architects must give shape to this proactiveness by acknowledging their ideas and suggestions. Any ignorance in this process may bring in negative effect of relational value on customer recommendation. Moreover, the effect of trust on customer recommendation is completely mediated by relational value. Thus, the results of the study have some important implications for an architect. Customers ought to be provided with innovative and unique architectural designs such as inspiration taken from different western countries and fusion for bringing variety. Also, an architect should check the feasibility of designs and execution of the plan. An architect can create value from other resource partners involved in the network, that is, by giving reference of the best suppliers for accessories like modular fittings to be used in the kitchen or washroom. Relational value can be created by motivating customers as well as involving customers' family members in key discussions. Also, being empathetic and understanding about any special need of the customer has a profound impact on the relational value. The customer should be periodically assured about the timely execution of the plans drafted since the completion of a house not only depends on the services of an architect, but also involves a whole network of resource partners, that is, appropriate material, labour, and other suppliers.